Analisis pelaksanaan program usaha kesehatan gigi sekolah (UKSG) di Sekolah Dasar Negeri 012 Samarinda Ulu Tahun 2019 - Nordianiwati, Nordianiwati; Meysarah, Farida (Journal of Oral Health Care, 2020)
The Analysis of The Implementation of The School Dental Health Business Program at SDN 012 Samarinda Ulu in 2019. Data networking class 1 SD of dental caries in the first place, namely Juanda Puskesmas elementary school students 012 2016 82 2017 96 2018 103 students as well as students. This study aims at analyzing the communication, surveillance and supervision on UKGS programs at 012 public elementary school Samarinda Ulu. Types of research is a qualitative phenomenological approach. Teachers informant UKGS Trustees, Principals, students at State Primary School 012 and holder UKGS Program in PHC Juanda. The data analysis technique that is data reduction, data display and verification. The results showed that there is no media communication in the schoolyard poster, target poor students remember the message, good supervision surveillance charge of the clinic, as well as the executive supervision of health centres and conducted annually by direct technique. Conclusions communication objectives and messages have not been appropriate, surveillance is good enough, the frequency is less appropriate supervision. Suggestions reproduce posters and banners are at school, the school budget cost control and increase the frequency of supervision.